Phūminām Čhangwat Phitsanulōk - Sanēhā Bunyarak (Khrōngkān Sưksā Khonkhwā Wičhai thāng Watthanatham, Samnak Sinlapawatthanatham, Sathāban Rātchaphat Phibūnsongkhrām, 1999)
Study on place names in Phitsanulok Province, Thailand.